Lead Levels in the Urine of Active Smokers and Passive Smokers in the Surroundings of Wadung Asri Sidoarjo - Juliana Christyaningsih; Qonita Salsabilla Amara Sherly Amri; Christ Kartika Rahayuningsih (International Journal of Advanced Health Science and Technology, 2023)
An active smoker is someone who smokes cigarettes, resulting in an impact on their health, as well as on passive smokers and the surrounding environment. Smoking exposes individuals to the risk of lead inhalation due to cigarette smoke. Accumulated lead from smoked cigarettes can pose a health risk. This study aimed to identify respondent characteristics and analyze lead levels in both active and passive smokers. The research employed a descriptive approach with quantitative analysis. The sample consisted of urine samples from 20 active and passive smokers in the vicinity of Wadung Asri, selected using purposive sampling. The study was conducted at the Toxicology Laboratory, TLM Department of the Health Polytechnic in Surabaya, and at BARISTAND from October 2022 to May 2023. Based on the characteristics of active and passive smokers, regarding age, those aged 21-44 accounted for 25% of active smokers and 30% of passive smokers, those aged 45-59 constituted 10% in both categories, and those aged 60-74 constituted 15% of active smokers and 10% of passive smokers. The study results revealed that lead levels in the urine of active smokers ranged from a high of 0.1592 µg/mL to a low of 0.0885 µg/mL. Conversely, in passive smokers, lead levels in the urine ranged from a high of 0.0885 µg/mL to a low of 0.000032 µg/mL. Thus, the conclusion drawn from this study is that one respondent exhibited lead levels exceeding the normal threshold of <0.15 µg/mL.